Heart rate recovery after orthostatic challenge and cardiopulmonary exercise testing in older individuals: prospective multicentre observational cohort study - Aaron James; David Bruce; Nicholas Tetlow; Amour B.U. Patel; Ethel Black; Nicole Whitehead; Anna Ratcliff; Alice Jamie Humphreys; Neil MacDonald; Gayle McDonnell; Ravishankar Raobaikady; Jeeveththaa Thirugnanasambanthar; et al. (BJA Open, 2023)
Background: Impaired vagal function in older individuals, quantified by the ‘gold standard’ delayed heart rate recovery after maximal exercise (HRRexercise), is an independent predictor of cardiorespiratory capacity and mortality (particularly when HRR ≤12 beats min−1). Heart rate also often declines after orthostatic challenge (HRRorthostatic), but the mechanism remains unclear. We tested whether HRRorthostatic reflects similar vagal autonomic characteristics as HRRexercise. Methods: Prospective multicentre cohort study of subjects scheduled for cardiopulmonary exercise testing (CPET) as part of routine care. Before undergoing CPET, heart rate was measured with participants seated for 3 min, before standing for 3 min (HRRorthostatic). HRRexercise 1 min after the end of CPET was recorded. The primary outcome was the correlation between mean heart rate change every 10 s for 1 min after peak heart rate was attained on standing and after exercise for each participant. Secondary outcomes were HRRorthostatic and peak VO2 compared between individuals with HRRexercise <12 beats min−1. Results: A total of 87 participants (mean age: 64 yr [95%CI: 61–66]; 48 (55%) females) completed both tests. Mean heart rate change every 10 s for 1 min after peak heart rate after standing and exercise was significantly correlated (R2=0.81; P<0.0001). HRRorthostatic was unchanged in individuals with HRRexercise ≤12 beats min−1 (n=27), but was lower when HRRexercise >12 beats min−1 (n=60; mean difference: 3 beats min−1 [95% confidence interval 1–5 beats min−1]; P<0.0001). Slower HRRorthostatic was associated with lower peak VO2 (mean difference: 3.7 ml kg-1 min−1 [95% confidence interval 0.7–6.8 ml kg-1 min−1]; P=0.039). Conclusion: Prognostically significant heart rate recovery after exhaustive exercise is characterised by quantitative differences in heart rate recovery after orthostatic challenge. These data suggest that orthostatic challenge is a valid, simple test indicating vagal impairment. Clinical trial registration: researchregistry6550.